Legal Protection for People with Mental Disabilities in the Criminal Justice System - Debi Masri; M. Salim; Junaidi Lubis; Grace Tan Mei Ling (Outline Publisher, 2025)
This study explores legal protection for individuals with mental disabilities within the international criminal justice system. While international conventions such as the United Nations Convention on the Rights of Persons with Disabilities (CRPD) provide a foundation for the basic rights of people with mental disabilities, the implementation of such protections within the criminal justice system remains limited. Many countries face challenges in providing adequate accommodations for people with mental disabilities during arrest, interrogation, and trial processes. This research examines the gap between international legal principles and their practical application, focusing on the mechanisms needed to support individuals with mental disabilities in both legal decisions and humane treatment. Additionally, the study explores how principles of legal capacity and supported decision-making can be integrated into existing legal frameworks, and the challenges faced in their implementation. The findings suggest the importance of adopting more inclusive policies and special accommodations to ensure that people with mental disabilities can enjoy their rights in the criminal justice process without discrimination. The paper recommends increased training for law enforcement officials and regulatory reforms that are more responsive to the needs of this group.